2014
DOI: 10.1007/s00264-014-2440-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficient derivation of osteoprogenitor cells from induced pluripotent stem cells for bone regeneration

Abstract: These findings indicate that our novel direct-plating method provides a clinically applicable, simple, and labour-efficient system for generating large numbers of homogeneous iPSC-derived osteoprogenitor cells for bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Previous studies have demonstrated the osteogenic potential of iPSCs (4,29). Although successful bone healing/ regeneration occurred when using these cells, teratoma formation was observed in 20% of the mice with transplanted osteogenically-induced iPSCs (30).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated the osteogenic potential of iPSCs (4,29). Although successful bone healing/ regeneration occurred when using these cells, teratoma formation was observed in 20% of the mice with transplanted osteogenically-induced iPSCs (30).…”
Section: Discussionmentioning
confidence: 97%
“…A previous study showed that rat BMMSCs showed increased proliferation and differentiation into a neurogenic lineage when grown on gelatin-coated plates as compared to noncoated plates, whereas adipose and osteogenic differentiation potentials were unaffected by gelatin [10]. In other studies using human or mouse derived iMSCs, osteogenic or chondrogenic differentiation potential was induced by gelatin or collagen coating, while they did not directly compare iMSC differentiation potential by deriving on the two types of substrates [3, 12, 15, 26]. The present study investigated for the first time how gelation or collagen coating affects the differentiation potential of derived iMSCs in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that iMSC characteristics such as differentiation potentials in vitro and in vivo are similar to those of primary progenitor cells [11], but it is not known whether extracellular components such as gelatin and collagen significantly affect iMSC characteristics in its derivation process. Although several studies have successfully reported the derivation of human iMSCs from iPSCs [3, 1214], a simple and efficient method for inducing mouse iMSCs has not yet been established [15, 16]. However, the safety of further clinical applications must be evaluated in appropriate animal models including genetically modified mouse, which requires the establishment of simple and effective derivation method for mouse iMSCs in addition to human cells.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to Other Types of Cells. The osteogenic differentiation ability of iPSCs-MSCs in comparison to MSCs was examined in a variety of studies [86,[93][94][95]. A study on iPSCs showed a delayed expression of osteogenic markers such as COL1A1 and bone sialoprotein (BSP) as well as weaker osteoblastic differentiation and mineral deposition, compared to human BM-MSCs in vitro [57].…”
Section: Osteogenic Differentiation Capability Of Ipscsmentioning
confidence: 99%